Simultaneous General Election: It Is Fair for Democracy in Indonesia - Kadir Johnson Rajagukguk; Sofjan Aripin; Heri Wahyudi (Universitas Pancasakti Tegal, 2021)
This study discusses the implementation of simultaneous elections in 2019 which is the decision of the Constitutional Court No. 14/PUU-11/2013 on simultaneous elections, and the purpose of this study is to examine and analyze whether the 2019 concurrent elections took place democratically and have a success rate to strengthen the consolidation of democracy and institutionalization of political parties in Indonesia. This research was conducted in North Sumatra, Banten, West Java and West Kalimantan. Furthermore, this study uses the theory of the pillars of the democratic system and the Theory of Success of Procedural and Substantive Quality Democracy. The method of research that is used is descriptive method with qualitative approach. With data analysis techniques. The findings show that the democratization of a concurrent election in 2019 is analyzed based on the pillars of a system that gives influence to the quality of the success rate of a democracy both procedural democracy and substantive democracy that measures the success rate of a democracy. Simultaneous elections in 2019 have increased public political participation and the Indonesian Democracy Index (IDI) but a new study is needed to measure the institutionalization of political parties so that comprehensively it can be known the level of democratization, consolidation of democracy and its relation to institutionalization or institutionalization of political parties.